Psychosocial Impacts of Mobile Game on K12 Students and Trend Exploration for Future Educational Mobile Games - Li, Yuanzhe; Xu, Zezheng; Hao, Yu; Xiao, Peng; Liu, Jingyan (Frontiers in Education, 2022)
Due to the popularity and advancement of 4G/5G networks, mobile games are currently becoming profitable tools for major internet platforms, which cover different, personalities and preferences. Mobile games are even refined to cover almost all age groups of the population, not just the young. Yet in the perception of the public, mobile games have always seemed to be associated with various derogatory terms such as interfering with learning, addiction and violence. K12 students are refer to the group of people who usually have less self-control capability, and they are undoubtedly the biggest advocates of mobile games. This paper summarizes the technological development of mobile games from the aspects of hardware and software. And a neutral perspective is given to analyse the psychological and social problems that mobile games have brought to K12 students. At the end of the paper, the insights of the future development of educational games and current limitations of mobile games are also addressed to explore the future trends of game-based education, that is, to bring education move closer to games, so that the students will not feel that they are learning purposely.